DISINFECTION AND STERILIZATION: THE ROLE OF CHEMISTRY IN THE FIGHT AGAINST COVID-19 - Ventura, Camilla (Revista Sistemática, 2020)
The COVID-19 pandemic highlighted the critical role of disinfection and sterilization in preventing viral transmission, particularly in healthcare and public environments. This article explores the chemistry behind effective disinfection methods, focusing on the mechanisms of action of key chemical agents such as alcohols, hydrogen peroxide, quaternary ammonium compounds, and chlorine-based disinfectants. It also addresses complementary physical methods like UV-C irradiation and their integration into sterilization protocols. Additionally, the article discusses the importance of proper application techniques, safety considerations, and environmental impacts associated with disinfectant use. Understanding the chemical principles underpinning disinfection is essential for developing safer, more effective, and sustainable strategies in the ongoing fight against COVID-19 and future infectious threats.